Analysis of the Communication Crisis Between Parents and Children Amid the Dominance of Social Media - Deas Valiyanida Hawa; Yani Achdiani; Sarah Nurul Fatimah (AMK : Abdi Masyarakat UIKA, 2026)
The rapid rise of social media has reshaped communication patterns within modern families, significantly influencing how parents and children interact in their daily lives. While social media platforms such as Instagram, TikTok, and WhatsApp provide convenience, entertainment, and a sense of connectedness, they have also contributed to a growing communication crisis within households. Many children increasingly engage with their digital devices, while parents similarly divide their attention between family responsibilities and online activities. This shift reduces face-to-face interactions, weakens emotional bonds, and widens generational communication gaps. This study analyzes the communication crisis caused by excessive social media dominance, exploring its impact on emotional closeness, family dynamics, and conflict emergence. It further examines the social and psychological factors that shape communication breakdowns between parents and children. The findings highlight that miscommunication often stems from digital distractions, differences in technological literacy, and shifting communication styles influenced by online culture. The study offers insights into how families can restore communication harmony through healthy digital habits, open dialogue, parental role modeling, and quality offline interaction. Strengthening emotional bonds is essential to prevent long-term relational damage and to ensure that technological advancement does not erode the foundation of parent–child relationships.